Mix design of porous asphalt mix (PAM) using steel slag as coarse aggregates for value-add applications - Erni Farisha Nor'Azhar (Nanyang Technological University, 2021)
With Singapore being a small tropical city-state, problems such as land scarcity and lack of construction materials has been around for many years. Moving towards sustainable construction, practising the 3Rs – reduce, reuse and recycle is a common practice in the construction industry. Steel slag, a by-product from the steelmaking industry has been reused and recycled in the making of the wearing coarse of roads in Singapore. With Singapore aiming to be a “Cycling Friendly City”, expanding the cycling path network to 800km by 2023, the feasibility of steel slag as coarse aggregates in the construction of porous asphalt mixture is studied. In short, the aim of this project is to evaluate the plausibility of incorporating steel slag as coarse aggregates and the effects it has on the performance of porous asphalt mixtures. Three experimental groups (GrA,GrB, GrC) with aggregates of different surface texture and angularity as coarse aggregates were studied. GrA being the control gradient, contains granite aggregates used as both the coarse and fine aggregates while GrB and GrC contains varying amounts of steel slag coarse aggregates. The specimens were cast by mixing the coarse aggregates with the granite fine aggregates, PG76 binder and hydrated lime fillers. In addition, instead of using the conventional PEN 60/70 binder, PG76 binder was used due to it being a polymer-modified binder and thus, have properties that are superior to PEN 60/70. To determine the right binder content for each experimental design, Draindown and Cantabro Abrasion Test were conducted first. The optimum binder content for experimental group A (granite as coarse aggregate) was found to be 4.5%, 5.5% for experimental group B (steel slag as coarse aggregates) and 5% for experimental group C (both granite and steel slag as coarse aggregates). Other performance tests were then conducted such as the Marshall Stability and Flow Test, Moisture Susceptibility Test, Indirect Tensile Test and Creep Test. Based on the Marshall Stability test, all three experimental groups satisfied the minimum requirement of 4.0kN Marshall Stability for low-strength pavements. In the Moisture Susceptibility test, the impact on stability was observed as there was a drop in stability but all three experimental groups still met the minimum requirement of 4.0kN. While for the repeated-load IDT, it is observed that GrB with steel slag coarse aggregates incorporated, produces the highest average mean resilient modulus. However, based on the Creep Test, GrA had a better result as compared to the other two experimental groups. Since both tests contradicts one another, it could be concluded that the superior mechanical properties of steel slag aggregates are not always prominent in all aspects.